Benthic and Fish Interactions With Pipeline Protective Structures in the North Sea - Redford, Michael; Rouse, Sally; Hayes, Peter; Wilding, Thomas A. (Frontiers in Marine Science, 2021)
An increasing number of pipelines and associated protective materials in the North Sea are reaching the end of their operational life and require decommissioning. Identifying the optimal decommissioning option from an environmental perspective requires an understanding of ecological interactions; currently there is little knowledge as to species associations with pipelines and associated protective materials. This study utilises industry ROV footage from the North Sea to quantify these interactions. A total of 58 taxa were identified, including 41 benthic taxa and 17 fish taxa. Taxa were grouped into seven groups for analysis including four groups for benthic epifauna: grazers, suspension/filter feeders, decapods, and colonial/encrusting taxa. Fish were organised into three groups: pollock, other fish, and other gadoids. Using zero-inflated generalised linear mixed models, we show that abundances of benthic epifauna and fish vary between types of protective structure (e.g. concrete mattresses, rock dump), depth, levels of fishing effort and proximity to oil and gas platforms. Six taxa groups exhibited higher abundances on concrete mattresses than bare pipelines with benthic epifaunal decapods showing the highest difference at 3.04 (1.83, 4.84, 95% CrI) times higher on mattresses compared to bare pipelines. Six groups were higher in abundance within the 500 m fisheries exclusion zone around platforms, compared to outside of the zone, with other gadoids showing the highest difference at 1.83 times (1.09, 2.89, 95% CrI) times higher inside zones. Five groups decreased in abundance with an increase in fishing effort, with the biggest effect observed with grazers decreasing in abundance at a rate of -28.01 % (-39.91, -13.88, 95% CrI) per 50 hours of fishing. We show that pipelines and protective materials are operating as artificial reefs, and our results suggest that removal of infrastructure could result in the loss of habitat and species.